Development of the Physics Practicum Apparatus based on Microcontroller: A Prototype Constructed from Misconceptions of Basic Kinematics Concepts - Syamsiah, Endah Nur; Taufani, Muhammad Rizka; Aminudin, Adam Hadiana; Pamungkas, Rahadian Sri; Fadilla, Reno Muhammad; Nabilah, Fatih Najah (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
This research aims to develop a prototype of the P-PAM (Physics Practicum Apparatus based on Microcontroller), specifically designed to address misconceptions in basic kinematics. The method employed for the prototype development follows the ADPT model (Analysis, Design, Prototyping, and Testing). The misconceptions identified during the analysis process include: (1) If the object's position is in the positive coordinate, it indicates that the object is moving forward; (2) The acceleration of an object is proportional to its instantaneous velocity. The practicum apparatus designed to address Misconception 1 is intended to measure the distance of an object, with data processed using Arduino Uno and transmitted to a PC via Bluetooth. The distance data is then processed using Python to generate information regarding distance, velocity, and acceleration, which are displayed in graphs over time. The apparatus for addressing Misconception 2 presents initial and final velocity data, as well as the acceleration of an object rolling past two sensors. The prototype of the first practicum apparatus can generate real-time graphs of position versus time and speed versus time. The second apparatus prototype provides initial velocity, final velocity, and acceleration data. Additionally, the device can demonstrate uniform acceleration for different initial speeds, as the incline is kept constant. There are 7 out of 10 acceleration data that fall within the confidence interval at the 96% confidence level. The prototype we created can present scientific facts from two misconceptions in basic kinematics material, in addition, our prototype can be used in learning that focuses on conceptual change.